Theory of Mind and Executive Functions in Children With Attention Deficit Hyperactivity Disorder and Specific Learning Disorder. Issue 5 (September 2021) - Singh, Jeetinder; Arun, Priti; Bajaj, Manoj Kumar
Background: Children with attention deficit hyperactivity disorder (ADHD) and specific learning disorder (SLD) generally have difficulties in social cognition and display impairments involving emotion and face and prosody perception and reduced empathy, indicating theory of mind (ToM) impairment. The objective of this work was to assess and compare the executive functions and ToM in children with ADHD and SLD. Methods: Twenty children diagnosed with ADHD, 20 children diagnosed with SLD, and 20 normal healthy children in the age group of 7 to 15 years, IQ between 90 and 110 (average intelligence) of any gender, were recruited. All participants were assessed using neuropsychological tests of executive functions and ToM. Results: Significant differences were found on early ToM, basic ToM, advanced ToM, and mean scores on ToM inventory between ADHD and control groups (P ≤ 0.001). Similarly, significant differences were found between ADHD and SLD groups on early, basic, advanced, and mean ToM inventory scores (P < 0.001). No significant differences were found between the control and SLD groups on ToM measures. Further, in the ToM task battery, on task D and task G, significant differences were found between the SLD and control groups at P = 0.04 and P = 0.03 respectively. Differences between ADHD and control groups were also statistically significant on task D and task G at P < 0.001 and P = 0.033. Executive functions in the form of set-shifting and response inhibition were significantly poor in the ADHD group and SLD group at P < 0.001 and P < 0.05 levels, respectively, when compared to the control group. Conclusion: Children with ADHD displayed more deficits in the ToM inventory and tasks than children having SLD and healthy children of their similar age and educational background. Executive functions (set-shifting and response inhibition) were poorer in children with ADHD and children with SLD when compared to healthy children of their similar age and educational background.